Exploring the Relationship Between Vertical Jump and Short Sprint Performance in Female Basketball Players - Raúl Nieto-Acevedo; Carlos García-Sánchez; Pablo Abián; Javier Abián-Vicén; Alfredo Sánchez-Bravo; Javier Díaz-Lara (Applied Sciences)
The aim of this study was to explore the relation between vertical jump and short sprint. A total of 14 female basketball players (n = 14; age: 20.9 ± 6.0 years; height: 177.0 ± 3.0 cm; body mass: 69.0 ± 11.1 kg) were assessed for Abalakov jump (ABKJ), countermovement jump (CMJ), and a 20 m sprint. The relationships between sprint and vertical jumps were analyzed using Pearson’s correlation coefficient and lineal regression, while discriminative parameters between backcourt and frontcourt players were assessed using independent t-tests. Higher associations were found between vertical jumps and sprint parameters, particularly CMJ height, showing a strong correlation with sprint time in 0–10 m (r = 0.805), 10–20 m (r = 0.798), and 0–20 m (r = 0.822). Jump metrics could provide a valid and reliable alternative for estimating sprint times over short distances in female basketball players. This finding could be an efficient alternative to save time in evaluations for team sports.